SUSTAINABLE BRANDING REVOLUTION: BUILDING AN ENVIRONMENTALLY CONSCIOUS BRAND AND INFLUENCING CONSUMER CHOICES - Farida Akbarina; Denpharanto Agung Krisprimandoyo; Reni Sara Indrawati; Muh Tabran; Iman Ahmad Gymnastiar (UIN Sunan Gunung Djati Bandung, 2023)
Sustainable branding is a socially and environmentally responsible approach for companies in the modern era. This research aims to analyze the role of sustainable branding in building a positive brand reputation and influencing purchasing decisions. The research method employs a literature review to integrate knowledge from various relevant sources. The discussion's outcomes indicate that consumer awareness of environmental issues is increasing, driving the demand for sustainable products. Sustainable branding strategies aid in establishing a favorable brand image among environmentally conscious consumers. Despite implementation challenges, innovation and ethics emerge as key factors to overcome these hurdles. In conclusion, sustainable branding plays a crucial role in cultivating a positive brand reputation and influencing purchasing decisions. Companies need to adapt to consumer trends and environmental concerns to achieve long-term success and amplify positive impacts on society and the environment.